2001
DOI: 10.1177/0306624x01455006
|View full text |Cite
|
Sign up to set email alerts
|

Family Interventions with Incarcerated Youth: A Review of the Literature

Abstract: Juvenile delinquency is a widespread societal problem threatening the well-being of families and communities throughout the country. In 1997, approximately 125,000 juveniles were incarcerated in public and private residential facilities as a result of a law violation. The rearrest rate for juveniles illustrates the need to develop effective interventions for incarcerated youth and their families. Although treatments focusing on the family as a unit may be more effective than individual treatment with delinquen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 70 publications
(104 reference statements)
1
36
0
Order By: Relevance
“…Parents of children referred for severe antisocial behavior maintained treatment gains in the way of reduced parent stress at one year following a parent management training group (Kazdin, Siegel, & Bass, 1993). Research on multifamily group therapy with juvenile offenders has proven to be the most effective intervention in affecting reduction of recidivism and improving family and youth functioning (Borduin et al, 1995;Hollin, 1999;Perkins-Dock, 2001). …”
mentioning
confidence: 99%
“…Parents of children referred for severe antisocial behavior maintained treatment gains in the way of reduced parent stress at one year following a parent management training group (Kazdin, Siegel, & Bass, 1993). Research on multifamily group therapy with juvenile offenders has proven to be the most effective intervention in affecting reduction of recidivism and improving family and youth functioning (Borduin et al, 1995;Hollin, 1999;Perkins-Dock, 2001). …”
mentioning
confidence: 99%
“…This work has long documented that there is a reduction in delinquent behaviors (measured by rearrests, recidivism, and truancy) when family therapy is used as a modality (Tolan, Cromwell, & Brasswell, 1986). Compared to individual treatment, family treatment has been shown to be more effective (Perkins-Dock, 2001). A recent meta-analysis of randomized controlled trials revealed that youths were less likely to spend time in juvenile detention and be re-arrested 1 to 3 years after treatment as a result of family interventions (Woolfenden, Williams, & Peat, 2009).…”
Section: Family-oriented Approaches and Evidencementioning
confidence: 99%
“…Support from family members, including parents, aunts, and children, has also demonstrated importance [20,21,[30][31][32]. For example, Muñoz-Laboy et al highlighted the role of family in protecting against depression, a consistent HIV risk factor, among formerly incarcerated Latino men [14,21,33].…”
Section: Introductionmentioning
confidence: 99%